“Ché non è impresa da pigliare a gabbo”: Dante’s Echoes in the "Scienza in cucina" by Pellegrino Artusi - Iosco, Valentina (ItaliAMO: Promotion of Italian Studies in the Academic and Non-Academic Environment, 2023)
In the wake of Unification of Italy, in Florence, Pellegrino Artusi publishes Science in the Kitchen and The Art of Eating Well, a book meant to get into the homes of all Italians and which contributed to the formation of an Italian of written and spoken use in the post-unification linguistic reality. This is not a simple cookbook: it welcomes, between one preparation and another, explicit references to Dante and the Comedy. Artusi demonstrates with good taste and common sense how Dante and the gastronomy are two strongly identifying elements for Italy. To highlight how deep this connection is, the text of the Science has been examined in search of implicit or explicit Dantean echoes. The intent of the research goes in two directions: on one hand, to hypothesize, through Artusi’s literary quotes, the type of public to which it is addressed, on the other, to highlight the educational purpose of the work, which cannot be considered only and simply a collection of recipes.